Epic poetry of the Trecento : Dante's Comedy, Boccaccio's Teseida, and Petrarch's Africa - Galligan, F (2004)
This thesis locates Dante's Divine Comedy (1307-1318), Boccaccio's Teseida (c.1340-1), and Petrarch's Africa (c. 1338-9) within a developing tradition of epic poetry. The works are usually treated separately, and are classed as epic to a varying degree, but I show that a reading of them as epic in light of each other enhances understanding of each, and illuminates more generally a history of the epic genre. I explore the extent to which the authors considered epic to be a distinct literary form, and counteract the notion that there was no conception of the genre in the Middle Ages. I show that similar responses to key areas of epic writing underlie surface differences between the poems. Where critics have tended to explore classical influences, I emphasise the importance of medieval epic texts for the formation of all three poems. I argue that in important respects the Comedy constitutes a new epic model for Petrarch and Boccaccio. I focus on Dante's development of the classical warrior hero into the contemporary Christian poet-hero, exploring his development of themes from 12th century Latin epics including the Anticlaudianus and Alexandreis. I suggest that the resulting emphasis on the theme of poetry is echoed in the Teseida and Africa. I argue that the Teseida revolves around issues of genre that are played out through the poems' gods and heroes, and that ultimately it resolves itself as a Dantean epic, through the hero Arcita. I show that the focus on poetry in the Africa, achieved both through the inclusion of poets as characters (including Petrarch himself) and by the explicit discussion of poetry within Book IX in particular, and the location of a Christian god at the heart of this historical narrative, reflect a treatment of key issues that bears similarity to that of Dante in the Comedy.